Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was working on a trig question and got stuck, but then I noticed a possible way to solve the problem. However, this way seemed to be slightly unconventional and possibly not what the book was looking for.

The question was: "Find $k$ and $b$ when $\sqrt3 \sin x + \cos x=k\sin(x+b)$" The first thing I did was to expand $k\sin(x+b)$ to $k\sin x\cos b+k\cos x\sin b$. Here is where I got stuck. I tried several different things, but I hit dead ends. Then I tried to equate coefficients and got $k\cos b=\sqrt3$ and $k\sin b=1$ which simplified to: $\cos b=\displaystyle{\sqrt3 \over k}$ and $\sin b=\displaystyle{1\over k}$. The answer from there is fairly simple to get which is $k=2$ and $b=\displaystyle{\pi\over6}$.

However this method seems rather dubious and so I was wondering if someone new a better way of solving the problem using more rigorous mathematical methods.

share|cite|improve this question
What makes it seem like a guessing game? Also, I believe you missed a solution. – Mike Dec 18 '11 at 1:54
$k^2=4$ has two solutions. – Henry Dec 18 '11 at 1:54
Good point. I just thought that using that method might not work all the, but I guess it might. – E.O. Dec 18 '11 at 1:56
Equating coefficients works here, but can be avoided by looking at the cases $x=0$ and $x=\pi/2$ and checking the final result. – Henry Dec 18 '11 at 1:56
up vote 3 down vote accepted

It's not at all dubious. The functions sin and cos are linearly independent and so $a_1 \sin x + b_1 \cos x = a_2 \sin x + b_2 \cos x$ for all $x$ iff $a_1=a_2$ and $b_1=b_2$.

To see that sin and cos are linearly independent, take $a \sin x + b \cos x = 0$ and set $x=0$ to get $b=0$ and $x=\pi/2$ to get $a=0$.

share|cite|improve this answer
This appears to be the only answer that explains why the OP's method is valid. +1 – Graphth Dec 18 '11 at 2:46
@Graphth, Henry's comment was also about this I think. – lhf Dec 18 '11 at 4:01
what about the case where $x=\pi /3$ – Ramana Venkata Dec 18 '11 at 5:17

I'm not sure how it's perceived as dubious. If you have $k \cos b = \sqrt{3}$ and $k \sin b = 1$, then you must $\frac{k \sin b}{k \cos b} = \tan b = \frac{1}{\sqrt{3}}$, which gets you $b = \frac{\pi}{6}$ or $\frac{7\pi}{6}$. From there it immediately follows that $k = 2$ or $-2$, respectively.

share|cite|improve this answer

If you have $k\cos b=\sqrt{3}$ and $k\sin b=1$, you should also remember that $k^2\cos^2 b+ k^2\sin^2 b= k^2$. That means $\sqrt{3}^2 + 1^2 = k^2$, so $k=\pm 2$. If you take $k=2$, you can find a suitable value of $b$, and with $k=-2$, you can find another.

share|cite|improve this answer

Suppose that $a\sin(x)+b\cos(x)=c\sin(x)+d\cos(x)$ holds for all $x$ in some neighborhood of $x_0$. Then we have the following equation and its derivative: $$ \begin{align} 0&=(a-c)\sin(x_0)+(b-d)\cos(x_0)\tag{1}\\ 0&=(a-c)\cos(x_0)-(b-d)\sin(x_0)\tag{2} \end{align} $$ Adding the squares of $(1)$ and $(2)$ gives $$ 0=(a-c)^2+(b-d)^2\tag{3} $$ Thus, $a=c$ and $b=d$.

So if we have $$ \begin{align} \sqrt{3}\sin(x)+\cos(x) &=k\sin(x+b)\\ &=k\cos(b)\sin(x)+k\sin(b)\cos(x)\tag{4} \end{align} $$ for all $x$ in some neighborhood of $x_0$, then we must have $$ k\cos(b)=\sqrt{3}\quad\text{ and }\quad k\sin(b)=1\tag{5} $$ and $(5)$ was solved above.

share|cite|improve this answer

Here is what I come up in my mind, maybe this is an unconventional way too: Divide both sides by $2$, we get $$\frac{\sqrt3}{2} \sin x +\frac{1}{2}\cos x=\frac{k}{2}\sin(x+b).$$ Note that $\displaystyle\sin(\frac{\pi}{6})=\frac{1}{2}$ and $\displaystyle\cos(\frac{\pi}{6})=\frac{\sqrt{3}}{2}$, the left hand side is given by $$\cos(\frac{\pi}{6})\sin x +\sin(\frac{\pi}{6})\cos x=\sin(x+\frac{\pi}{6}),$$ where the last equality follows from compound angle forumula. Combining these, we have $$\sin(x+\frac{\pi}{6})=\frac{k}{2}\sin(x+b).$$

share|cite|improve this answer

Here is a standard trick to deal with expressions of the type $A \sin(x) + \cos(x)$:

Let $u$ be so that $\cot(u) =A$.

Then, after bringing everything to the same denominator, your expression becomes

$$A \sin(x) + \cos(x)= A\frac{\cos(u) \sin(x)+\sin(u)\cos(x)}{ \sin(u)} =\frac{ \sin(x+u)}{\sin(u) }$$

If you look over the other answers, this is exactly what they did, in a non-explicit way.

Remark If instead you use $\tan(v)=A$, you end up with

$$A \sin(x) + \cos(x) = \frac{\cos(x-v)}{\cos(v)} \,.$$

Same substitutions also solve the expressions of the type $\sin(x) + B\cos(x)$.

share|cite|improve this answer

In general, $$\begin{align*} \alpha \sin(x) + \beta \cos(x) &= \sqrt{\alpha^2+\beta^2}\left(\frac{\alpha}{\sqrt{\alpha^2+\beta^2}}\sin(x) + \frac{\beta}{\sqrt{\alpha^2+\beta^2}}\cos(x)\right)\\ &= \sqrt{\alpha^2+\beta^2}\left(\cos(y)\sin(x) + \sin(y)\cos(x)\right)\\ &= \sqrt{\alpha^2+\beta^2}\sin(x+y) \end{align*}$$ where $y$ is the angle whose cosine is $\dfrac{\alpha}{\sqrt{\alpha^2+\beta^2}}$ and whose sine is $\dfrac{\beta}{\sqrt{\alpha^2+\beta^2}}$. In your problem, $\alpha = \sqrt{3}, \beta = 1$, which readily gives $k = 2$, $b = \frac{\pi}{6}$. As others have pointed out, this misses one of the two solutions.
If $\sqrt{\alpha^2+\beta^2}$ (which conventionally means the positive square root) is replaced throughout by $({\alpha^2+\beta^2})^{1/2}$, we get the other solution $k = -2, b = \frac{7\pi}{6}$ upon choosing $({\alpha^2+\beta^2})^{1/2} = -2$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.